2005
DOI: 10.1007/s00411-005-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB in bone marrow cells of BALB/cJ mice following exposure in vivo to low doses of 137Cs γ-rays

Abstract: We measured levels of NF-kappaB activation in bone marrow (BM) cells collected at 1 and 4 h from male BALB/cJ mice (10-12 weeks old) given a whole body dose of 0, 0.05, 0.1 and 1 Gy of (137)Cs gamma-rays (at the dose rate of 0.75 Gy/min). At each harvest time-point, BM cells were collected from five mice per dose of radiation. We used two methods for detecting NF-kappaB activation (1) the NF-kappaB/p65 transcription factor enzyme-linked immunosorbance assay (ELISA) and (2) immunofluorescence staining with NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…These cytokines were selected for analyses because high levels of their expression have been detected in the BM, spleen, macrophages, and mesenteric lymph nodes of mice exposed to varying doses of radiation (ranging from 0.05 to 8.0 Gy) [26,[30][31][32][33], including human blood mononuclear cells obtained from healthy adult individuals who lived near the Chernobyl Nuclear Power Plant and were chronically exposed to low-dose radiation ranging from 0.18 mSv to 49 mSv [34]. Nuclear extract kits (Active Motif North America, Inc., Carlsbad, CA, USA) were used for obtaining cytosolic and nuclear fractions.…”
Section: Measurement Of Levels Of 8-oh-dg In Bm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines were selected for analyses because high levels of their expression have been detected in the BM, spleen, macrophages, and mesenteric lymph nodes of mice exposed to varying doses of radiation (ranging from 0.05 to 8.0 Gy) [26,[30][31][32][33], including human blood mononuclear cells obtained from healthy adult individuals who lived near the Chernobyl Nuclear Power Plant and were chronically exposed to low-dose radiation ranging from 0.18 mSv to 49 mSv [34]. Nuclear extract kits (Active Motif North America, Inc., Carlsbad, CA, USA) were used for obtaining cytosolic and nuclear fractions.…”
Section: Measurement Of Levels Of 8-oh-dg In Bm Cellsmentioning
confidence: 99%
“…There were four groups of male CBA/CaJ mice, 10-12 weeks old at exposure (20 mice per group, making a total of 80 mice), given an acute whole body dose of 0 or 3.0 Gy of 137 Cs ␥ rays (at the dose rate of 0.7 Gy/min) using the GammaCell 40 (Atomic Energy of Canada, Ltd., Ontario, Canada) located in the Division of Laboratory Animal Resources of Stony Brook University. Exposure procedures, as described previously [26], were followed. A dose of 3.0 Gy of 137 Cs ␥ rays, which is approximately half of the LD 50/30 value for the CBA/Ca mouse [27,28], was used because it is known to cause toxicity to BM and other tissues of humans and mice.…”
Section: Chemicalsmentioning
confidence: 99%
“…The activation of the NF-jB pathway by ionizing radiation in general is known (Brach et al, 1991) as well as by e.g. c-radiation in particular (Rithidech et al, 2005;Jung et al, 1998). To the knowledge of the authors, NF-jB activation by b-radiation has not yet been described.…”
Section: Biological Activity Of the Space Radiation Source Pm-147: Nfmentioning
confidence: 93%
“…Inhibition of NF-κB activity reduces chemoresistance to 5-fluorouracil (5-FU) in human stomach cancer. Ionising radiation (IR) has been reported to activate NF-κB in both in vitro and in vivo studies (Rithidech, 2005;Ahmed, 2006). Laszlo et al recently reported that IkB-alpha depletion in the late phase of IR is a result of a combined regulation at both transcription and translation levels (Laszlo, 2008).…”
Section: Nf-κb -A Key Playermentioning
confidence: 99%